Appointment of Isha Ambani and Akash Ambani as Directors - Reliance Industries Limited (2022)
Isha Ambani and Akash Ambani are appointed as Directors on the Boards of Reliance Jio Infocomm Limited and Reliance Retail Ventures Limited.